2018
DOI: 10.31940/soshum.v8i1.776
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students' Speaking Ability through Scaffolding Technique

Abstract: Students often got confused and felt hesitant when they speak English. This situation had caused poor speaking ability, which then lead to serious problem in the teaching-learning process.  The application of scaffolding technique in the EFL learning might be the ideal solution; it had some principles that could improve the students’ speaking ability. This research is aimed at finding out the effect of the implementing Scaffolding Technique towards the students’ speaking ability. Participants were 50 (27 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The obtained results of the present study corroborate those of Ginaya et al (2018), who investigated the impact of scaffolding on learners' speaking abilities. The findings revealed that trainees' speaking abilities had improved.…”
Section: Discussionsupporting
confidence: 90%
“…The obtained results of the present study corroborate those of Ginaya et al (2018), who investigated the impact of scaffolding on learners' speaking abilities. The findings revealed that trainees' speaking abilities had improved.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it is necessary to repeat the directions that have been delivered before to make sure they do not lose the points, and it will help them to evaluate information rapidly before moving on to the next lesson. Moreover, when the teacher repeats the direction, the voice supposed to be clear, as quoted from (Ginaya et al, 2018) that by repeating again and again for some sentence in the direction with clear voice, the students will listen well.…”
Section: Resultsmentioning
confidence: 99%